C - reactive protein predictive marker value and its significance in management of pre dialysis chronic kidney disease patients when correlated with total serum proteins and serum albumin levels: experience in a teaching institution - Arora, Balvinder Singh; Biswal, Indu; Sen, Poornima; Rajan, Santhosh; Ali, Amjad; Rajwanshi, Prabal (International Journal of Advances in Medicine, 2017)
Background: Chronic kidney disease (CKD) is imposing newer challenges, not only globally, but, also in India, especially managing the end stage renal disease (ESRD). Screening for CKD at an early stage, by, high sensitivity C reactive protein (hsCRP) with or without other clinical, biochemical or anthropometric parameters helps initiate specific therapy to reduce the progression of renal disease. Although, malnutrition, inflammation and cardio vascular diseases (CVD) have been shown as significant independent risk factors of mortality in CKD patients, but, whether there exists any relationship between hsCRP and serum proteins and serum albumin levels, one of the important indicators of PEM, has not been extensively studied in pre-dialysis CKD patients. Methods: The study included a total of 60 adult subjects. Of these, 30 were study cases who fulfilled the case definition of CKD and were compared with 30 patients who did not show any signs or symptoms of CKD. As per the objective - hsCRP values were estimated by ELISA test, quantified and statistically correlated with total serum proteins and albumin levels. Results: A significant difference was found in the mean value of hsCRP in cases and in controls (p value 0.001). No significant difference was observed in the mean level of total serum protein in cases and controls, but, the mean differences in the level of serum albumin between cases and controls was significant. The association of serum albumin and hsCRP was found to be significant (p value <0.001). If a level of serum albumin < 3.5 is taken as a marker of malnutrition, it is found that 66.66% of patients have hypo-albuminaemia. Conclusions: The present study comes to an important conclusion that hsCRP is a useful independent predictor of CKD and if correlated with serum albumin levels, it would help clinician manage the patient effectively by initiating an aggressive yet very appropriate therapy at the pre-dialysis stage with the likelihood of an ‘evidence based’ reduction in morbidity and mortality.